Making Money from Photography : In Every Conceivable Way - Bavister, Steve; Edited by Baber, Neil (Cincinnati, Ohio David & Charles, 2007)
In this comprehensive manual, Steve Bavister gives an invaluable insight into the business of being a photographer, with tips and examples of how to take great pictures in every genre, including: advice on shooting and selling stock photography, how to get your work into picture libraries, successful strategies for wedding and portrait photography, and inspirational, high-quality examples from top photographers Tips on running your own photography business.
Include Colored Illustration, Indexes
Assistant Editor Louise Clark
Keywords: Photography--Business methods -- Photography--Marketing -- Commercial photography